Forms of document falsification in Malaysia’s Syariah courts - Wan Abdul Fattah Wan Ismail (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Documents including old and outdated ones have come to be a vital meeans of proving evidence as long as the features are legible and permanent .This opens the door for document forgery or falsification. This article examined the the forms of document falsification in Malaysia’s Syariah courts as perceived by 181randomly and purposeful sampled syarie judges, syarie officers, syarie lawyers, lecturers and syariah and law students, and forensic experts, Syariah and Civil Practitioners practitioners in Selangor, Negeri Sembilan, and Federal Territory of Kuala Lumpur and Putrajaya. The study found signature forgeries and factual alterations of medical certificates to be the most prevalent forms of document falsification. They were unpredictable and vared with time and opportunity. Such incidence of falsification was perceived as moderate by respondents. Interestingly, the Syariah courts had not given much attention to the document falsification when it is clear that this would impair judgements and decisions. It is time that a complete forensic model on document falsification, in line with principles of Islamic law, should be developed for the Syariah courts to serve as guidelines for Syariah legal practitioners and judges.